2017
DOI: 10.1016/j.aquatox.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Up-stream mechanisms for up-regulation of miR-125b from triclosan exposure to zebrafish (Danio rerio)

Abstract: A B S T R A C TTriclosan (TCS) exposure has widely adverse biological effects such as influencing biological reproduction and endocrine disorders. While some studies have addressed TCS-induced expression changes of miRNAs and their related down-stream target genes, no data are available concerning how TCS impairs miRNA expression leading us to study up-stream regulating mechanisms. Four miRNAs (miR-125b, miR-205, miR-142a and miR-203a) showed differential expression between TCS-exposure treatments and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…These results from zebrafish are inconsistent with those in mice concerning changes in miR-125b and fat accumulation. Lin et al (2017) demonstrated that triclosan induced an estrogen effect that acted on the novel estrogen receptor GPER leading to over-expression of miR-125b and further hepatic steatosis, while not on the classical ERα and ERβ. It is assumed that miR-125b influences fat-metabolism disorders through estrogen effects; however, the receptors identified in various reports are different (Li et al, 2015;Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results from zebrafish are inconsistent with those in mice concerning changes in miR-125b and fat accumulation. Lin et al (2017) demonstrated that triclosan induced an estrogen effect that acted on the novel estrogen receptor GPER leading to over-expression of miR-125b and further hepatic steatosis, while not on the classical ERα and ERβ. It is assumed that miR-125b influences fat-metabolism disorders through estrogen effects; however, the receptors identified in various reports are different (Li et al, 2015;Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2017) demonstrated that triclosan induced an estrogen effect that acted on the novel estrogen receptor GPER leading to over-expression of miR-125b and further hepatic steatosis, while not on the classical ERα and ERβ. It is assumed that miR-125b influences fat-metabolism disorders through estrogen effects; however, the receptors identified in various reports are different (Li et al, 2015;Lin et al, 2017). Currently, NAFLD is the most common chronic liver disease worldwide and is a major public health concern in modern society (De Alwis and Day, 2008;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In general, estrogens bind with two classes of receptors: nuclear hormone receptors (ERα and ERβ) that are ligand-dependent transcription factors, and the G protein-coupled estrogen receptor (GPER, also known as GPR30), an integral membrane protein. Lin et al (2017) reported that TCS acted on GPER, but not conventional receptors (ERα and ERβ). Additionally, high throughput RNA-seq identified differentially expressed genes induced by TCS or BPA exposure varied greatly because of their different estrogenic target molecules (Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of four miRNAs, miR-125b, miR-205, miR-142a, and miR-203a were significantly modulated by TCS in different experimental models both in vivo and in vitro ( 55 ), and resulted implicated in the downstream regulation of genes responsible for FA synthesis and metabolism. Moreover, in zebrafish, TCS was directly involved in the upstream regulation of miR-125b ( 68 ).…”
Section: Effects Of Edcs Exposure On Lipid Metabolism In Animal Modelmentioning
confidence: 99%